2015
DOI: 10.1111/psyg.12158
|View full text |Cite
|
Sign up to set email alerts
|

First magenetic resonance imaging studies on aluminium maltolate‐treated aged New Zealand rabbits: an Alzheimer's animal model

Abstract: The present study makes this animal model a substantial one for further molecular level studies and opens up new targets for potential therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
1
0
0
Order By: Relevance
“…Another finding of our study was that JWR rabbits fed a 2% cholesterol diet showed significant cortical and hippocampal atrophy, in accordance with current clinical standards for AD [ 16 18 , 41 ].Similar to previous studies based on New Zealand White rabbit model of AD [ 42 ], cholesterol-fed JWR rabbits provided support for one of the most consistent findings in AD—an ventricular enlargement. In our study, the atrophy of the hippocampus is more evident than the cortex in cholesterol-fed rabbits, and the enlargement of the lateral ventricle adjacent to the hippocampus is more evident than the third ventricle.…”
Section: Discussionsupporting
confidence: 89%
“…Another finding of our study was that JWR rabbits fed a 2% cholesterol diet showed significant cortical and hippocampal atrophy, in accordance with current clinical standards for AD [ 16 18 , 41 ].Similar to previous studies based on New Zealand White rabbit model of AD [ 42 ], cholesterol-fed JWR rabbits provided support for one of the most consistent findings in AD—an ventricular enlargement. In our study, the atrophy of the hippocampus is more evident than the cortex in cholesterol-fed rabbits, and the enlargement of the lateral ventricle adjacent to the hippocampus is more evident than the third ventricle.…”
Section: Discussionsupporting
confidence: 89%